Ultrasound-Assisted Extraction of Patin Fish Oil: Optimization Using Response Surface Methodology – Box Behnken Design - Putri, Anggita Rosiana; Setyaningsih, Widiastuti; Palma, Miguel; Fernandez, Ceferino Carrera; Rohman, Abdul; Riyanto, Sugeng; Jang, Young Pyo (Universitas Gadjah Mada, 2025)
The oil extracted from Pangasius micronemus, commonly known as patin fish, is highly regarded for its omega-3 and omega-6 fatty acids content, which offer numerous health benefits. Producing high-quality patin fish oil (PFO) rich in these essential fatty acids requires an optimized extraction process. This study utilized ultrasound-assisted extraction (UAE) combined with response surface methodology – Box Behnken Design (RSM-BBD) to optimize the extraction of PFO. Five variables were examined: temperature (30–60 °C), solvent composition (n-hexane in isopropanol, 30–90%), amplitude (30–90%), solvent-to-sample ratio (10:1–20:1), and cycle duration (0.2–0.8 s−1). The analysis identified solvent composition, amplitude, and solvent-to-sample ratio as significant factors influencing the response value (p < 0.005). Optimal UAE conditions were achieved at a temperature of 59 °C, solvent composition of 42%, amplitude of 41%, solvent-to-sample ratio of 20:1, cycle duration of 0.8 s−1, and an extraction time of 25 min. Fatty acid profiling revealed that PFO extracted using UAE contained omega-3 fatty acids, including α-linolenic acid (ALA) at 1.36% and eicosapentaenoic acid (EPA) at 0.46%, as well as omega-6 fatty acids, namely linoleic acid (LA) at 19.06% and arachidonic acid (AA) at 0.85%. These results demonstrate the efficiency of UAE in extracting high-quality PFO.